LIRT: A Lightweight Scheme for Indistinguishability, Reachability, and Timeliness in Wireless Sensor Control Networks - Wei Ren; Liangli Ma; Yi Ren (International Journal of Distributed Sensor Networks, 2013)
Wireless sensor control networks (WSCNs) are important scenarios and trends in mobile wireless sensor networks. Compared with traditional wireless sensor networks, WSCNs have two specific characteristics: entities in networks are extended from passive sensors to active sensors (e.g., actuators and actors) and the transmitting messages are extended from data only to data plus (e.g., data and control instructions). Thus new security problems arises. In this paper, we make the first attempt to specify the security requirements for WSCNs, namely, indistinguishability, reachability, and timeliness. In addition, several new attacks in WSCN, distinguishing risks, dropping attacks, and disordering attacks, are pointed out at the first time. A lightweight scheme LIRT is proposed with tailored design to guarantee the indistinguishability, reachability, and timeliness in WSCNs. Extensive and rigorous analysis on LIRT justifies its security strength and performance measures.